Revista de Revistas - Boyd-Bowman, Peter (Nueva Revista de Filología Hispánica (NRFH), 2007)
RECENT LITERATURE OF THE RENAISSANCE: A BIBLIOGRAPHY, págs. 265-452. PUBLICATIONS OF THE MODERN LANGUAGE ASSOCIATION OF AMERICA, Menasha, Wisconsin, 1947